Innovative materials to build a better infrastructure development - Putra Jaya, Ramadhansyah; Munirwan, Reza Pahlevi; Bunyamin, Bunyamin (Popular Scientist, 2024)
It is with great pleasure that we introduce the launch of the Smart and Green Materials journal for 2024. In this inaugural issue, we explore innovative materials for advancing infrastructure development. The issue also delves into various strategies aimed at enhancing materials to improve their properties. In our rapidly evolving world, researchers are increasingly seeking materials with versatile properties tailored for diverse demanding applications, such as insulation for construction buildings. The goal is to tackle environmental protection and energy-saving building issues more efficiently, and one of the key focuses of our journal is to disseminate knowledge in this field. In addition, most of the articles published in this issue fulfill this goal in particular. The research showcased in this inaugural issue underscores significant advancements in theory, experimentation, and methodology, providing solutions to pressing challenges.